A new potential energy surface for the H(2)S system and dynamics study on the S((1)D) + H(2)(X(1)Σ(g)(+)) reaction - Yuan, Jiuchuang (Sci Rep, 2015)
We constructed a new global potential energy surface (PES) for the electronic ground state ((1)A′) of H(2)S based on 21,300 accurate ab initio energy points over a large configuration space. The ab initio energies are obtained from multireference configuration interaction calculations with a Davidson correction using basis sets of quadruple zeta quality. The neural network method is applied to fit the PES, and the root mean square error of fitting is small (1.68 meV). Time-dependent wave packet studies for the S((1)D) + H(2)(X(1)Σ(g)(+)) → H((2)S) + SH(X(2)Π) reaction on the new PES are conducted to study the reaction dynamics. The calculated integral cross sections decrease with increasing collision energy and remain fairly constant within the high collision energy range. Both forward and backward scatterings can be observed as expected for a barrierless reaction with a deep well on the PES. The calculated integral cross sections and differential cross sections are in good agreement with the experimental results.